Transition metal-catalyzed (remote) deconjugative isomerization of α, β-unsaturated carbonyls. (27th April 2022) - Scaringi, Simone; Mazet, Clément
Graphical abstract: Abstract: The seemingly counter-intuitive transition metal-catalyzed deconjugative isomerizations of α, β-unsaturated carbonyls offer novel perspectives within the context of remote functionalization strategies. This Digest provides an overview of the handful of examples that have been reported over the last two decades in this area.